Comprehensive life cycle assessment of 25 furniture pieces across categories for sustainable design - Dongfang Yang; Carlo Vezzoli; Hang Su (Scientific Reports)
Abstract Furniture is a crucial sector for sustainable development due to its high environmental impact and substantial potential for sustainable improvement. Despite many existing furniture Life Cycle Assessment (LCA), they often provide fragmented data, hindering a comprehensive understanding of the environmental impact across different furniture groups due to methodological disparities. This study employs LCA as the primary method to evaluate 25 furniture pieces across 8 groups. Using the Environmental Footprint method and the Ecoinvent 3.7 database within Simapro 9.1.1.1 software, it generates a comprehensive database with all 25 furniture pieces’ environmental performance data, including the environmental impacts of furniture with different characteristics within the same furniture group, the impacts of various life cycle stages for each piece, and the impacts of different materials/processes within each stage. The database highlights several trends: furniture groups with higher material weight generally exhibit greater environmental impact; the pre-production stage generally has the highest impact, followed by the production, distribution, end-of-life and use stage. For environmental data interpretation, the study provides valuable design priorities, suggestions, and opportunities for improving the environmental performance, supported by case studies. By uncovering common trends, this research informs and guide the pursuit of more sustainable furniture design and production practices.